2013
DOI: 10.1038/nrgastro.2013.117
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal manifestations and complications in IBD

Abstract: More than one-third of patients with IBD are affected by extraintestinal manifestations or extraintestinal complications beyond the intestinal manifestation of the disease. The most common manifestations include arthropathies, mucocutaneous and ophthalmological manifestations, as well as conditions affecting the hepatobiliary system, both in Crohn's disease and ulcerative colitis. However, less frequent manifestations, such as pulmonary or neurological manifestations, should also be considered in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
245
1
21

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(272 citation statements)
references
References 114 publications
5
245
1
21
Order By: Relevance
“…Multiple other organ systems can be affected in IBD patients, including bones and joints, skin and eyes [22,23]. In our case series, 8 of 13 (62%) patients had extraintestinal manifestations; all had IBD-associated arthritis/arthropathy.…”
Section: Discussionmentioning
confidence: 94%
“…Multiple other organ systems can be affected in IBD patients, including bones and joints, skin and eyes [22,23]. In our case series, 8 of 13 (62%) patients had extraintestinal manifestations; all had IBD-associated arthritis/arthropathy.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have reported that as many as 30% of patients with IBD have at least one extraintestinal manifestation, such as pyoderma gangrenosum (PG), erythema nodosum, polyarthritis, or iritis (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Bone loss is considered to be a disabling complication of inflammatory bowel disease (IBD) (1). Bone mineral density (BMD) testing results of patients with IBD from seven medical facilities, ranging from January 1996 to October 2006, were reviewed to determine the prevalence rate of osteoporosis (2).…”
Section: Introductionmentioning
confidence: 99%